Flow in a fibril-forming disease - Schönland, Stefan; Hegenbart, Ute (Blood, 2017)
In this issue of Blood, Muchtar and colleagues report on the prognostic value of multiparametric flow cytometry (MFC) to measure clonal plasma cell burden at diagnosis and at end of treatment in patients with amyloid light-chain (AL) amyloidosis.